Internet shutdowns and the limits of law - De Gregorio, G; Stremlau, N (USC Annenberg Press, 2020)
Internet shutdowns are on the rise. In the past few years, an escalation of this blunt censoring practice has affected different regions of the world, particularly Africa and Asia. Scholars and advocates have proposed no substantive solutions to effectively address Internet shutdowns, and analysis has largely been limited to examining the negative effects through data about their frequency, duration, and economic costs. This article attempts to move beyond the polarized debate between “keep it on” and “shut it off” to explore how there can be more transparency around decision-making processes behind Internet shutdowns. We also discuss the limits of law when it comes to the imposition and implementation of shutdowns. Shutdowns tend to be imposed somewhat arbitrarily with little process. Bringing back legal arguments into the exploration of the justifications around shutdowns may make the use of shutdowns less frequent and more limited, when they do occur.